2015
DOI: 10.3109/19401736.2015.1022762
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rapid assay to detect the jellyfish Cyanea nozakii using a loop-mediated isothermal amplification method

Abstract: Blooms of the harmful jellyfish Cyanea nozakii, which are a severe nuisance to fisheries and tourisms, frequently occur in the northern East China Sea, Yellow Sea, and Bohai Sea. To provide early warning of this species, a simple and effective molecular method for identifying C. nozakii was developed using the loop-mediated isothermal amplification method (LAMP). The LAMP assay is highly specific and uses a set of four primers that target six different regions on the mitochondrial cytochrome c oxidase subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Since every cell contains hundreds of mitochondrial DNA copies, it makes mitochondrial encoded sequences ideal targets for molecular detection requiring high sensitivity, as is the case for O. volvulus detection in skin biopsies [41]. For this reason, the cox 1 gene has already been used as a target for other molecular assays to detect the presence of the jellyfish Cyanea nozakii in seawater samples or the presence of the olive tree pest Bactrocera oleae in the guts of arthropods [42, 43]. It will be of interest for future work to study whether a correlation exists between number of mf as determined by microscopy and time to LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Since every cell contains hundreds of mitochondrial DNA copies, it makes mitochondrial encoded sequences ideal targets for molecular detection requiring high sensitivity, as is the case for O. volvulus detection in skin biopsies [41]. For this reason, the cox 1 gene has already been used as a target for other molecular assays to detect the presence of the jellyfish Cyanea nozakii in seawater samples or the presence of the olive tree pest Bactrocera oleae in the guts of arthropods [42, 43]. It will be of interest for future work to study whether a correlation exists between number of mf as determined by microscopy and time to LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…The BLAST search of the 18S region showed that the C. nozakii in the present study was 100% identical to C. nozakii (KT445894) collected from Chinese coastal waters. As noted previously, C. nozakii is widely distributed around the coasts of China, Korea, and Japan (Dong et al 2008 ; Hong and Lin 2010 ; Liu et al 2016 ). Therefore, 18S and 28S rDNA can be utilized to easily detect and monitor this harmful organism in the marine environment.…”
Section: Discussionmentioning
confidence: 66%
“…The jellyfish Cyanea nozakii Kishinouye 1891 belongs to the family Cyaneidae and is commonly known as the ghost jellyfish. The species is widely distributed around the coasts of China, Korea, and Japan (Dong et al 2008 ; Hong and Lin 2010 ; Liu et al 2016 ). It can be industrially used as a source of collagen for immune-enhancing activity (Tang et al 2013 ; Zhang et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations